Triphenylamine‐Functionalized Multiple‐Resonance TADF Emitters with Accelerated Reverse Intersystem Crossing and Aggregation‐Induced Emission Enhancement for Narrowband OLEDs. (8th January 2023) - Chen, Guowei; Wang, Jianghui; Chen, Wen‐Cheng; Gong, Yarong; Zhuang, Ning; Liang, Hui; Xing, Longjiang; Liu, Yuan; Ji, Shaomin; Zhang, Hao‐Li; Zhao, Zujin; Huo, Yanping; et al.
Abstract: Multiple‐resonance (MR) thermal activated delayed fluorescence (TADF) emitters have attracted increasing attention in organic electroluminescence devices, owing to their superior quantum efficiency and narrowband emission for high color purity. However, MR‐TADF materials often suffer from severe aggregation‐caused quenching (ACQ) and efficiency roll‐off problems due to their rigid planar structures and the lack of sufficient charge‐transfer (CT) characters with inefficient reverse intersystem crossing (RISC). Herein, by attaching electron‐rich triphenylamine (TPA) with twisted spatial conformation to the MR framework, two efficient narrowband MR‐TADF emitters, namely BNCz‐pTPA and BNCz‐mTPA, are developed. The TPA substituent endows the new emitters with aggregation‐induced emission enhancement (AIEE) for ACQ suppression. The unprecedented AIEE‐MR‐TADF emitters exhibit CT character in high‐lying triplet excited states for faster RISC, while the locally‐excited (LE) character of the first singlet excited state is retained for narrowband emission with high emission efficiency. An organic light‐emitting diode (OLED) based on BNCz‐pTPA exhibits a maximum external quantum efficiency of 27.3% with slow efficiency roll‐off, demonstrating much higher performances than those of the BNCz ‐based OLED. This study may provide a simple but effective approach to constructing high‐performance emitters for wide‐color‐gamut OLED displays. Abstract : Two triphenylamine‐functionalized multiple‐resonance thermally activated delayed fluorescence materials are developed and simultaneously show accelerated reverse intersystem crossing and aggregation‐induced emission enhancement characteristics for aggregation‐caused quenching suppression. Highly efficient narrowband organic light‐emitting devices with external quantum efficiencies as high as 27.6% with reduced efficiency roll‐offs are demonstrated.